Atividade das enzimas do sistema purinérgico em plaquetas de pacientes com mieloma múltiplo - Andrade, Sabrina Fontana de (2016)
Multiple myeloma (MM) is characterized as a tumor of plasma cells which corresponds to approximately 10 % of haematological malignancies. Nowadays it is considered as an incurable disease, which can present complications such as bleeding or thrombosis. Hemostasis is the balance between procoagulant and anticoagulant systems aiming to prevent blood loss. The enzymes ectonucleotidases present on platelet surface are responsible for the regulation of extracellular levels of adenine nucleotides. ADP and ATP, as well as the nucleoside adenosine have been involved in a large number of physiological functions: ADP is the main platelets recruitment factor, while ATP is a competitive inhibitor of ADP-induced aggregation. Adenosine is a molecule able to induce vasodilation and inhibit platelet aggregation. Platelet activation process is accompanied by the secretion of platelet proteins such as platelet factor 4 (PF4) and increased formation of thromboxane (TXA2). Considering these concepts the aim of this study was to evaluate the activity of ecto-enzymes (E- NTPDase, 5'- nucleotidase and E -ADA) in platelets and measuring concentration of PF4 and TXA2 in patients with MM. The results showed a reduction in the E-NTPDase activity for ATP hydrolysis in both treated (p<0,001) patients and in those who were not receiving treatment (p<0,05) for MM in the period of blood samples collection. This reduction can result in a decrease in extracellular levels of ADP, as this enzyme is responsible for conversion of ATP into ADP, which would reduce platelet aggregation in patients with MM. When we evaluated the enzyme E- 5'- nucleotidase, no statistical difference was observed concerning its activity in these patients. An increase in E- ADA activity (p<0,001) was observed in patients with MM performing treatment, this may have occurred as a physiological response to increase of adenosine in these patients. Adenosine has vasoprotective and antiplatelet property and its increase can be related to the medicines used for these patients. Dosages of PF4 and TXB2 (stable metabolite of TXA2) showed lower values of these substances in MM untreated (p< 0,05; p< 0,001) and MM treated patients (p< 0,01; p< 0,001) in the control group. These data reveal a lower capacity aggregation and platelet activation in patients with MM, and highlight the participation of purinergic signaling in hemostasis in these patients.